Enhanced biological desalination by Arthrospira platensis: Role of extracellular polymeric substances in ion adsorption and salt removal - Mostafa E. Elshobary; Roham Sanjari; Sten Littmann; Joachim Henjes; Stephan SW. Ende (Journal of Environmental Management, 2026)

Spontaneous sequential desalination as a promising strategy for biological salt removal and production of value-added compounds from microalgae - Reham Ebaid; Joachim Henjes; Dieter Hanelt; Stephan Ende (Journal of Water Process Engineering, 2025)

Synergistic microalgal cocultivation: Boosting flocculation, biomass production, and fatty acids profile of Nannochloropsis oculata and Phaeodactylum tricornutum - Mostafa E. Elshobary; Reham Ebaid; Mohammed Alquraishi; Stephan S.W. Ende (Biomass and Bioenergy, 2025)

Nanomaterials in aquaculture disinfection, water quality monitoring and wastewater remediation - Silvanir; Wei Han Foo; Wen Yi Chia; Stephan Ende; Shir Reen Chia; Kit Wayne Chew (Journal of Environmental Chemical Engineering, 2024)

Recent advances in recirculating aquaculture systems and role of microalgae to close system loop - Stephan Ende; Joachim Henjes; Marc Spiller; Mostafa Elshobary; Dieter Hanelt; Abdelfatah Abomohra (Bioresource Technology, 2024)

Robust deep learning based shrimp counting in an industrial farm setting - Christina Bukas; Frauke Albrecht; Muhammad Saeed Ur- Rehman; Daniel Popek; Mikołaj Patalan; Jarosław Pawłowski; Bert Wecker; Kilian Landsch; Tomasz Golan; Tomasz Kowalczyk; Marie Piraud; Stephan S.W. Ende (Journal of Cleaner Production, 2024)

Developing an economically efficient LED light regime for Arthrospira platensis cultivation - Agnese Stunda-Zujeva; Stephan Ende; Megija Berele; Albert Beyer (Journal of Applied Phycology, 2023)

New microalgae media formulated with completely recycled phosphorus originating from agricultural sidestreams - Albert S. Beyer; Jasmin Meier; Marina Jiménez-Muñoz; Raphael Meixner; Stephan S. W. Ende; Abdelfatah Abomohra; Joachim Henjes (Journal of Applied Phycology, 2023)
This study investigated the impact of struvite as a sustainable phosphorus source on the growth and phycocyanin production by the blue-green alga Arthrospira platensis . Three modified growth media were compared to the typical SAG-spirul culture media. CS(+) refers to the completely recycled struvite from bovine urine as a phosphate source, while S(-) and S(+) refer to commercially available struvite as a phosphate source. On media with (+), a pre-treatment was conducted to evaporate NH 4 , as it negatively affects cell growth and functions of the photosynthetic apparatus at high concentrations, and to release phosphate due to the low solubility of struvite in water. For each medium, three cultures were cultivated in Erlenmeyer flasks for a duration of 42 days. Results showed that no statistically significant negative effect of struvite was found on the growth rates. However, C-phycocyanin (CPC-P) in CS(+) and S(+) was significantly higher compared to CPC-P in untreated growth media. The study hypothesized that low concentrations of NH 3 remaining after the pre-treatment of struvite could have a positive impact on phycocyanin accumulation, as an energy efficient and quick nitrogen source for A. platensis .

Heterotrophic microalgae production on food waste and by-products - Stephan S. W. Ende; Anja Noke (Journal of Applied Phycology, 2019)